Indian Tourism Websites with Special Reference to the Selected States: A Webometrics - Muniyasamy, M.; Nanthakumar, M.; Kumar, K. Sathish (Innovare Journal of Education, 2023)
Webometrics studies the quantitative aspects of the construction and use of information resources, structures, technologies on the web, and informetric approaches. Webometrics is concerned with measuring characteristics of the web: websites, web pages, and parts of web pages, words in web pages, hyperlinks, and web search engine results. This study investigates and explores the websites of 18 selected Indian Tourism websites based on their external backlinks, Edu backlines, Gov backlinks, Edu domains, Gov domains, Global Rank, PR quality, and desktop and mobile website loading time of state tourism in India. This study collected data from Check page rank and other SEO-analyzer search engines. The researcher suggested that Indian Tourism websites need to attract more external backlinks and the global level by introducing creative online sources and services and updates of news and information. Identify and analyze global Rank and PR quality websites of Indian Tourism.